Bacteriophages and Bacterial Plant Diseases - Buttimer, Colin; McAuliffe, Olivia; Ross, R. P.; Hill, Colin; O’Mahony, Jim; Coffey, Aidan (Frontiers in Microbiology, 2017)
Abstract Losses in crop yields due to disease need to be reduced in order to meet increasing global food demands associated with growth in the human population. There is a well recognised need to develop new environmentally-friendly control strategies to combat bacterial crop disease. Current control measures involving the use of traditional chemicals or antibiotics are losing their efficacy due to the natural development of bacterial resistance to these agents. In addition, there is an increasing awareness that their use is environmentally unfriendly. Bacteriophages, the viruses of bacteria, have received increased research interest in recent years as a realistic environmentally friendly means of controlling bacterial diseases. Their use presents a viable control measure for a number of destructive bacterial crop diseases, with some phage-based products already becoming available on the market. Phage biocontrol possesses advantages over chemical controls in that tailor-made phage cocktails can be adapted to target specific disease-causing bacteria. Unlike chemical control measures, phage mixtures can be easily adapted for bacterial resistance which may develop over time. In this review, we will examine the progress and challenges for phage-based disease biocontrol in food crops.